1989
DOI: 10.1099/00222615-29-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Ultrastructure of Infected Kidney Stones

Abstract: Summary. Struvite stones are formed as the result of urinary tract infection by ureaseproducing bacteria. Ultrastructural examination of calculi removed from a patient revealed bacteria incorporated throughout the stone matrix. Exopolysaccharide stained by ruthenium red was associated with most of the bacteria, but it represented only a small portion of the organic matrix in the stone. Localised deposits of calcium and phosphorus, components of carbonate-apatite, and magnesium, a struvite component, were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Only a few models have been published for studying apatite mineralization in vitro (19)(20)(21), e.g.,: (i) Bacterial models of (kidney) stones using bacteria having urease and often AP activity (22,23). (ii) Osteoblastic cell cultures for studying bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few models have been published for studying apatite mineralization in vitro (19)(20)(21), e.g.,: (i) Bacterial models of (kidney) stones using bacteria having urease and often AP activity (22,23). (ii) Osteoblastic cell cultures for studying bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few models have been published for studying apatite mineralization in vitro (19)(20)(21), e.g.,: (i) Bacterial models of (kidney) stones using bacteria having urease and often AP activity (22,23). (ii) Osteoblastic cell cultures for studying bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…which has the ability to form crystals inside the host cells (7), but other bacterial species such as Pseudomonas spp., Escherichia coli or Staphylococcus aureus are also involved in nephrolithiasis (8). After calculi development, the germs can survive in the inorganic matrix, where the antibiotics do not penetrate, thus the persistent infection can determine the growth of calculi in all the kidney cavities (calyx, pelvis) in time of weeks or months (9). Several studies showed that the urinary lithiasis can be induced by chronic or persistent UTI (so-called "infection-induced stones").…”
Section: Introductionmentioning
confidence: 99%